2020
DOI: 10.1038/s41416-020-0802-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of MRX34, a liposomal miR-34a mimic, in patients with advanced solid tumours

Abstract: Background In this first-in-human, Phase 1 study of a microRNA-based cancer therapy, the recommended Phase 2 dose (RP2D) of MRX34, a liposomal mimic of microRNA-34a (miR-34a), was determined and evaluated in patients with advanced solid tumours. Methods Adults with various solid tumours refractory to standard treatments were enrolled in 3 + 3 dose-escalation cohorts and, following RP2D determination, expansion cohorts. MRX34, with oral dexamethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
464
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 560 publications
(469 citation statements)
references
References 49 publications
2
464
1
2
Order By: Relevance
“…In fact, MRX34, a liposomal miR-34a mimic, is the first human phase I clinical trial of miRNA cancer therapy in all patients with advanced solid tumors [ 171 ]. Although the trial was closed early due to serious immune-mediated adverse effects that resulted in the death of four patients, the dose-dependent modulation of relevant target genes provides proof-of-concept for miRNA-based cancer therapy [ 172 ]. The combination treatment with miR-34a has been shown to enhance the anti-tumor activity of other anti-cancer agents (γ-secretase inhibitor, sirtinol and zoledronic acid) in MM cells, through various mechanisms [ 173 ].…”
Section: Mirnas Therapeutic Strategies In MMmentioning
confidence: 99%
“…In fact, MRX34, a liposomal miR-34a mimic, is the first human phase I clinical trial of miRNA cancer therapy in all patients with advanced solid tumors [ 171 ]. Although the trial was closed early due to serious immune-mediated adverse effects that resulted in the death of four patients, the dose-dependent modulation of relevant target genes provides proof-of-concept for miRNA-based cancer therapy [ 172 ]. The combination treatment with miR-34a has been shown to enhance the anti-tumor activity of other anti-cancer agents (γ-secretase inhibitor, sirtinol and zoledronic acid) in MM cells, through various mechanisms [ 173 ].…”
Section: Mirnas Therapeutic Strategies In MMmentioning
confidence: 99%
“…They are relatively non-toxic, and because of their size, they have less chance to induce an immune response. A phase 1 study with MRX34, a liposomal miR-34a mimic, showed manageable toxicity profile in most patients and some clinical activity in HCC patients [193]. Although the study needed to be terminated because of serious adverse effects in some patients, it established the proof-of-concept for miRNA-based therapy.…”
Section: Resultsmentioning
confidence: 99%
“…As the maximum tolerated dose was revealed to be 110 mg/m 2 in patients without hepatocarcinoma, a high incidence of adverse events (e.g., 100% all grades and 38% grade 3 among all patients), such as fever, fatigue, back pain, nausea, diarrhea, anorexia, and vomiting, was found among patients with liver cancer receiving treatment with MRX34 (10-50 mg/m 2 , i.v., biweekly) who required palliative management with dexamethasone premedication. Nevertheless, MRX34 did exhibit antitumor activity among patients with refractory advanced solid tumors (Beg et al, 2017;Hong et al, 2020), offering valuable insight into the development of miRNA therapeutics.…”
Section: B Types Of Rna Drugs and Mechanisms Of Actionmentioning
confidence: 99%